FISHES OF THE LOWER STRETCH OF RIVER TAWA, MADHYA PRADESH AND CONSERVATION NEEDS - BOSE, A. K.; JHA, B. C.; SURESH, V. R.; DAS, A. K.; RIDHI, MS; SHARMA, A. P. (Journal of the Inland Fisheries Society of India, 2021)
An assessment of fish diversity of river Tawa recorded 47 fish species representing 6 order, 14 families and 30 genera. Cyprinidae was the most dominant family (51.06%) followed by Bagridae (8.51%) and Ambassidae (6.38%). Fifteen species were ornamental (31.91%), 4 aquacultural species (8.51%), 3 Game fish (6.38%), 4 Aquaculture+Game fish (8.51%), 3 Aquaculture+Ornamental fish (6.38%), 2 Minor commercial (4.25%), 3 Minor commercial+Ornamental fish (6.38%), 1 Minor commercial+Gamefish+Ornamental (2.12%), 1 SF- Subsistence fisheries (2.12%), and 5 no interest fish (10.63%). Conservation status of fishes revealed that 3 (6.38%) species have not been evaluated, 1 (2.12%) species was vulnerable, 39 (82.97%) species were of least concern, 1 (2.12%) species was data deficient and 3 (6.38%) species were near threatened.Key words: River Tawa, fish diversity, distribution, human use, conservation status.